Synthesis of hollow and spherical cadmium sulphide nanoparticles by an unconventional design of bioelectrochemical system. (10th November 2021) - Ho, Cuong Tu; Lam, Thuong Thuong; Nguyen, Hanh Thi; Nguyen, Canh Xuan; Le Dang, Quang; Lee, Ji-hoon; Yang, Youri; Hur, Hor-Gil
The synthesis of CdS nanoparticles was developed based on the unconventional design of bioelectrochemical system (BES) inoculated with Shewanella sp. HN-41. The BES configuration included two bottle chambers separated by silicon membrane but directly connected by a graphite electrode perforating through silicon membrane, namely, non-external circuit bioelectrochemical system (nec_BES). Shewanella sp. HN-41 in the anode of nec_BES consumed lactate and transferred electrons to the graphite electrode end in the anode and, in its turn, the graphite electrode end in the cathode reduced directly thiosulfate to sulphide, forming CdS nanoparticles after 21 days. CdS nanoparticles with the average size of approximately 17 nm were synthesized in the cathode solution. The hollow, spherical, and void structure of particles was observed by transmission electron microscopy (TEM) and scanning electron microscopy (SEM) images. The energy dispersive X-ray spectroscopy (EDS) study confirmed the nanoparticles contained Cd and S elements, and X-ray diffraction (XRD) data showed a strong crystalline phase and mixed crystallites of CdS nanoparticles. The UV-Vis absorption spectra of CdS nanoparticles revealed the blue shift in excitonic transition with respect to CdS bulk material, suggesting its potential application in optical studies. The bioelectrochemical system can be applied for the removal and preparation of other sulphide heavy metals.